Synthesis of Thieno[2,3-d]imidazoles by Copper-Catalyzed Amidine Cyclization - Liubchak, Kostiantyn; Tolmachev, Andrey; Nazarenko, Kostiantyn (Synlett, 2014)
A new synthetic approach to thieno[2,3-d]imidazoles is presented on the basis of the N′-(3-halothiophen-2-yl)amidine cyclization under copper-catalyzed cross-coupling. Using commercially available starting materials such as 2-aminothiophenes or their Boc-protected derivatives and copper catalysts, this method offers a convenient route to a wide range of thieno[2,3-d]imidazole derivatives, especially the 5-alkyl-subtituted thieno[2,3-d]imidazoles.
Keywords: amidines; cyclization; copper; thiophenes; imidazoles